Effect of vibrator parameters and physical characteristics of parts on conveying velocity - Vellingiri, Vishwa Priya (Strojniški vestnik, 2023)
Automation is generally employed in the area of orienting, lifting, and moving parts for production in industries including automotive, electronic, food, and packaging. With the help of automation, it is possible to reduce the manufacturing time and labour required. The most adaptable tools for feeding small, designed pieces during part assembly are vibratory feeders. Industries have been effectively using vibratory feeders for more than 30 years, indicating that such technology is advanced. Although research in this area has not been lacking, a fundamental understanding of the interactions between a part’s physical characteristics and the various vibratory feeder operating parameters in relation to optimal performance, defined as conveying a part with maximum stability and maximum velocity, remains lacking in linear feeders. While several papers discuss the effect of vibratory parameters (excitation frequency and amplitude of vibration) and the coefficient of friction, the effect of characteristics of part (l/w ratio and mass) is neglected. In this work, the effect of these factors on the conveying velocity of prismatic parts made of aluminium and brass on a horizontal track without inclination was determined, and an attempt was made to develop a predictive model based on the above factors. Using Taguchi’s design of experiments (DOE), an L16 orthogonal array was designed. A response table for the signal-to-noise ratio has yielded optimal values for each parameter taken into consideration. ANOVA predicted frequency as the most influential parameter, followed by the coefficient of friction. The regression analysis yields an R2 value of 99.3 % for aluminium and 98.7 % for brass. The results of the regression model and random experiments show a high correlation of 91.66 %. This model is required to set the desired conveying velocity of parts so that continuous flow can be maintained in automated assembly or packaging industries.
Keywords: ANOVA; coefficient of friction; conveying velocity; količnik trenja; l/w ratio; linear vibratory feeders; linearni vibracijski dodajalniki; masa; mass; razmerje d/š; transportna hitrost; zasnova eksperimentov po Taguchiju